THE MUTUAL DIALECTIC OF HISTORICAL MEMORY AND CONSCIOUSNESS IN THE WORLDVIEW - Ruziev Anvar Jumanazarovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article analyzes the philosophical essence of the concepts of historical consciousness and memory, their role as a factor guaranteeing the development of society. Approaches to the essence of historical consciousness, which helps to gain a deeper understanding of the content of historical memory, are studied comparatively.